Sustainable commercial interiors - Bonda, Penny (John Wiley & Sons, Inc., 2007)
Millions of people in the U.S. workforce rely on interior designers to create environments that make them happy and productive, as well as promote their safety and well-being. Sustainable Commercial Interiors provides an engaging introduction to and exploration of the vast field of sustainable design as it specifically relates to commercial interior spaces. In Sustainable Commercial Interiors, coauthors Penny Bonda, a noted expert on interior design and sustainability, and Katie Sosnowchik, an interior design editor and innovator, share their passion for environmental advocacy while offering designers and architects the technical knowledge important for success in this evolving discipline. The authors apply the concept of environmental responsibility to the design of interiors, and employ the organization of the LEED Green Building Rating System(r) to sort the design process into five categories: sustainable sites, water efficiency, energy issues, materials, and indoor environmental quality.